2007
DOI: 10.1007/s10562-007-9172-z
|View full text |Cite
|
Sign up to set email alerts
|

Peroxyacetic Acid Oxidation of Olefins and Alkanes Catalyzed by a Dinuclear Manganese(IV) Complex with 1,4,7-trimethyl-1,4,7-triazacyclononane

Abstract: Natural terpenes, (-)-limonene and (+)-carvone, can be epoxidized by peroxyacetic acid (PAA) at room temperature if a dinuclear manganese(IV) complex with 1,4,7-trimethyl-1,4,7-triazacyclononane (L), [Mn 2 L 2 O 3 ] [PF 6 ] 2 , is used as a catalyst. The total yield of the epoxides based on the consumed olefins are 97 and 95%, respectively. A kinetic study of the dec-1-ene and cyclohexane oxygenations including the investigation of their simultaneous competitive oxidation was carried out. The olefin epoxidatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 72 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…The use of PAA for the degradation of pollutants in wastewater has also been studied by some researchers. In particular, activation of PAA by energy (UV or solar) or catalysts [e.g., Fe­(II/III), Co­(II/III), Mn­(II/III/IV), Ru­(III), V­(IV/V), and activated carbon] creating advanced oxidation conditions has shown high efficiency for the removal of a variety of organic pollutants. ,,, The enhanced removal of pollutants, compared to PAA alone, is derived from the formation of reactive radical species, such as • OH and CH 3 C­(O)­OO • , which were confirmed by electron paramagnetic resonance (EPR) analysis and/or radical quenching experiments. ,,,, The reaction mechanism and reactivities of organic compounds with respect to radicals formed from activated PAA should be different from those of direct oxidation by PAA. This review paper focuses on the reaction of compounds by PAA, not by activated PAA.…”
Section: Background Of Paamentioning
confidence: 99%
“…The use of PAA for the degradation of pollutants in wastewater has also been studied by some researchers. In particular, activation of PAA by energy (UV or solar) or catalysts [e.g., Fe­(II/III), Co­(II/III), Mn­(II/III/IV), Ru­(III), V­(IV/V), and activated carbon] creating advanced oxidation conditions has shown high efficiency for the removal of a variety of organic pollutants. ,,, The enhanced removal of pollutants, compared to PAA alone, is derived from the formation of reactive radical species, such as • OH and CH 3 C­(O)­OO • , which were confirmed by electron paramagnetic resonance (EPR) analysis and/or radical quenching experiments. ,,,, The reaction mechanism and reactivities of organic compounds with respect to radicals formed from activated PAA should be different from those of direct oxidation by PAA. This review paper focuses on the reaction of compounds by PAA, not by activated PAA.…”
Section: Background Of Paamentioning
confidence: 99%
“…Previous research has employed a variety of metals, such as Fe­(II/III/VI), Co­(II/III), Mn­(II/III/IV), Ru­(III), and V­(IV/V), to activate PAA. , , Among them, Fe is environmentally abundant and benign. The Fenton reaction was first discovered by Fenton, and it has been applied for pollution remediation since the late 1960s .…”
Section: Introductionmentioning
confidence: 99%
“…A relevant soluble polymer-bound Mn(IV) complex with N-alkylated 1,4,7-triazacyclononane was used as a catalyst in the H 2 O 2 oxygenation of alkanes [82]. We have also demonstrated that alkanes and olefins can be oxidized by tert-butyl hydroperoxide [72,95,96] or peroxyacetic acid [81,97] using complex 1a as a catalyst. The reaction with tert-butyl hydroperoxide is significantly accelerated in the presence of a small amount of a carboxylic acid [72,96].…”
Section: Introductionmentioning
confidence: 99%